2021
DOI: 10.1080/1068316x.2021.1962866
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of recidivism following release from custody: a meta-analysis

Abstract: The reliable identification of those offenders at greatest risk of post-release recidivism is critically important given the emotional and financial costs associated with offending behaviour. The aim of the current study was to synthesise the available literature on risk predictors to identify which factors are predictive of recidivism in adult offenders, in the four years following release from custody. After systematically reviewing the literature and selecting those at least risk of bias, 43 high quality st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 111 publications
(109 reference statements)
1
20
0
Order By: Relevance
“…It may be that problematic behaviors in school are better predictors of recidivism than educational level, which may confound multiple noncriminogenic characteristics, such as IQ, motivation, or learning style. A recent meta-analysis of risk factors for recidivism reached results similar to ours concerning the mediocre predictive validity of educational level (Goodley et al, 2022). As to Item 22 (No prosocial activities), there seemed to be no sample selection explanations for its lackluster predictive validity.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…It may be that problematic behaviors in school are better predictors of recidivism than educational level, which may confound multiple noncriminogenic characteristics, such as IQ, motivation, or learning style. A recent meta-analysis of risk factors for recidivism reached results similar to ours concerning the mediocre predictive validity of educational level (Goodley et al, 2022). As to Item 22 (No prosocial activities), there seemed to be no sample selection explanations for its lackluster predictive validity.…”
Section: Discussionsupporting
confidence: 84%
“…The two most predictive items were Items 7 and 8, which covered, respectively, institutional misconduct and breach of release conditions. The behaviors described by these items are known risk factors of general recidivism (Goodley et al, 2022) and figure in multiple criminological risk scales, such as the STABLE-2007 (Brankley et al, 2021; Hanson et al, 2007) and the PCL-R. In addition, an upcoming study based on machine learning algorithms concluded that these two items were the most predictive of general recidivism in a sample very similar to the one used in the current study (Arbour et al, 2022).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Relatedly, a recent meta-analysis by Goodley et al [27], regarding predictors of recidivism following release from custody, found that while there is significant heterogeneity with respect to predictors of recidivism across the extant literature, the authors identified 17 factors with sufficient evidence from the published studies reviewed that were associated with either an increase or decrease in recidivism. Importantly, many of these factors were not necessarily directly related to SUD and were generally categorized by the authors into factors related to: History of Criminal Behavior, Antisocial Personality Pattern, Antisocial Cognitions and Antisocial Companions, all of which have been previously described by Andrews and colleagues [1,27]. Two additional factors related to increased risk for recidivism identified by Goodley et al included history of mental illness and race, with the latter posited to reflect the larger context of racial inequality in CJ involvement in the US [27].…”
Section: Is Recidivism An Appropriate Outcome?mentioning
confidence: 99%
“…Importantly, many of these factors were not necessarily directly related to SUD and were generally categorized by the authors into factors related to: History of Criminal Behavior, Antisocial Personality Pattern, Antisocial Cognitions and Antisocial Companions, all of which have been previously described by Andrews and colleagues [1,27]. Two additional factors related to increased risk for recidivism identified by Goodley et al included history of mental illness and race, with the latter posited to reflect the larger context of racial inequality in CJ involvement in the US [27]. It is also important to acknowledge that SUD treatment alone may be unlikely to significantly impact many of the factors identified above by Goodley et al, which is why we believe that recidivism may not be the most appropriate outcome to assess for CJ-involved individuals with an SUD.…”
Section: Is Recidivism An Appropriate Outcome?mentioning
confidence: 99%